Mutation analysis in glutaric aciduria type I. Issue 3 (1st March 2000) - Zschocke, Johannes; Quak, Elfriede; Guldberg, Per; Hoffmann, Georg F
Abstract : Glutaric aciduria type 1 (GA1), resulting from the genetic deficiency of glutaryl-CoA dehydrogenase (GDH), is a relatively common cause of acute metabolic brain damage in infants. Encephalopathic crises may be prevented by carnitine supplementation and diet, but diagnosis can be difficult as some patients do not show the typical excretion of large amounts of glutaric and 3-hydroxyglutaric acids in the urine. We present a rapid and efficient denaturing gradient gel electrophoresis (DGGE) method for the identification of mutations in the glutaryl-CoA dehydrogenase ( GCDH ) gene that may be used for the molecular diagnosis of GA1 in a routine setting. Using this technique, we identified mutations on both alleles in 48 patients with confirmed GDH deficiency, while no mutations were detected in other patients with clinical suspicion of GA1 but normal enzyme studies. There was a total of 38 different mutations; 27 mutations were found in single patients only, and 21 mutations have not been previously reported. Fourteen mutations involved hypermutable CpG sites. The commonest GA1 mutation in Europeans is R402W, which accounts for almost 40% of alleles in patients of German origin. GCDH gene haplotypes were determined through the analysis of polymorphic markers in all families, and three CpG mutations were associated with different haplotypes, possibly reflecting independent recurrence. The high sensitivity of the DGGE method allows the rapid and cost efficient diagnosis of GA1 in instances where enzyme analyses are not available or feasible, despite the marked heterogeneity of the disease.